(untitled) (Quinto Sol, 2016)
This article analyzes the Araguaya steamboat’s case, a luxurious ship that left the Southampton Port (England) to Río de Janeiro and Buenos Aires ports in 1910. During the trip there was a cholera outbreak that spread on board only among the third class passengers who were immigrants.In the first part of the article, we explain how traveling conditions in the steerage were decisive for the outbreak. In the second part, we describe the case in detail, from the departure of the ship until its arrival at a quarantine hospital in Brazil. In the early twentieth century, knowledge and techniques of bacteriology began to take part in health protocols ports of South America for diagnosis and control conditions. Under the aegis of the bacteriology, the Araguaya case makes possible a historical questioning of the experience with diseases during the transatlantic voyage of European workers to America in the late 19th and early 20th century.